Most Commercial Ready-to-Eat Foods in and Around Universities in Eastern Uganda Contain Pathogenic Drug-Resistant Bacteria: A Call to Action - Abdul Walusansa; Shaban Okurut A.; Jamilu E. Ssenku; Ali Kudamba; Nulu Nansikombi; Sumin Lunkuse; Hannington Oryem-Origa (Journal of Food Innovation, Nutrition, and Environmental Sciences)
Uganda faces an escalation of drug-resistant foodborne bacterial diseases. Academic communities such as universities are among the most affected but the burden is under researched. Hence, this study determined the prevalence of drug-resistant bacteria and the associated factors in food, in and around Islamic University in Uganda, to inform and support the way forward. Conventional culture, microscopy, biochemical characterization and disk diffusion methods were used to identify drug resistant, medically important bacterial pathogens from a random sample of 79 ready-to-eat commercial foods. Focus Group Discussions were used to examine the factors enabling the presence of these pathogens in food, among a random sample of 67 food vendors. Data were analyzed using thematic analysis and descriptive statistics with STATA version 15, and World Health Organization guidelines. Escherichia coli (30.1%, n=47) and Staphylococcus aureus (20.5%, n=32) were the most prevalent, while Shigella spp. (1.1%, n=2) was the least. The Total Viable Load of cooked foods (0.91×10¹ CFU/g) and deep-fried fast foods (1.52×10¹ CFU/g) met safety limits, but fresh fruit (3.44×10⁴ CFU/g) and vegetable salads (3.58×10⁴ CFU/g) exceeded WHO standards. Total Coliform Counts in all samples were unsafe, with fresh fruit (3.30×10⁴ CFU/g) and vegetable salads (1.15×10⁴ CFU/g) showing the highest contamination. Many isolates were drug-resistant, including E. coli to Cefoxitin (48%) and Imipenem (18%), and S. aureus to Nalidixic acid (38%) and Gentamycin (26%). Contamination was mainly linked to food handlers' practices (23.5%, n=8) and sociodemographic factors (17.6%, n=6). Stricter hygiene measures and better food safety monitoring are urgently needed.